Diagnostic utility of clinical and laboratory test parameters for differentiating between sudden acquired retinal degeneration syndrome and pituitary‐dependent hyperadrenocorticism in dogs. (12th March 2019) - Oh, Annie; Foster, Melanie L.; Williams, Jonathan G.; Zheng, Chaowen; Ru, Hongyu; Lunn, Katharine F.; Mowat, Freya M.
Abstract: Objective: To identify discriminating factors, using clinical ophthalmic examination findings and routine laboratory testing, that differentiate dogs with early sudden acquired retinal degeneration (SARDS; vision loss <6 weeks' duration), age‐ and breed‐matched control dogs, and dogs with pituitary‐dependent hyperadrenocorticism (PDH). Animals: Client‐owned dogs: 15 with SARDS with <6 weeks duration of vision loss, 14 age‐ and breed‐matched control dogs, and 13 dogs with confirmed PDH. Procedures: Dogs underwent ophthalmic examination, electroretinography (ERG) fundus photography, and spectral‐domain optical coherence tomography (SD‐OCT) in addition to physical examination, urinalysis, serum biochemistry, complete blood count, and adrenocorticotrophic hormone (ACTH) stimulation testing. Statistical analysis was performed using receiver operating curve area under the curve analysis, principal component analysis with sparse partial least squares analysis, and one‐way ANOVA. Results: Dogs with SARDS all had absent vision and ERG a‐ and b‐waves. SD‐OCT demonstrated that dogs with SARDS had significantly thicker inner retina, thinner outer nuclear layer, and thicker photoreceptor inner/outer segment measurements than either controls or dogs with PDH. Discriminating laboratory parameters between dogs with SARDS and PDH with high specificity included post‐ACTH serum cortisol (<19.3 μg/dL), AST:ALT ratio (>0.343), and urine specific gravity (>1.030). Conclusions and Clinical Relevance: We have identified significant discriminators between SARDS and PDH. This work provides the basis for future studies that could identify and examine dogs with SARDS prior to vision loss, which may extend the potential therapeutic window for SARDS.